2018
DOI: 10.1145/3181854
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment of CS doctoral programs shows strong correlation with faculty citations

Abstract: IMAGERY FROM SHUTTERSTOCK.COM counts of papers published in computer science journals and number of highly cited faculty). The final ranking is a weighted average of these measures. The scientometrics community criticized this approach because the choice of weights is not clearly justified. 4,6 The U.S. News ranking of doctoral programs in engineering b uses a weighted average of objective measures and subjective measures. As with the ARWU, justification for the ranking formula is lacking.Ranking of computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Comparing citation counts with statistical significance requires an order-of-magnitude difference in the citation counts [30], which limits their utility in making fine-grained choices. Despite these quality issues, recent work [56] has demonstrated that citation-based metrics can be used to build a university ranking that correlates highly with peer assessment; we show that our method provides a similar quality of correlation.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Comparing citation counts with statistical significance requires an order-of-magnitude difference in the citation counts [30], which limits their utility in making fine-grained choices. Despite these quality issues, recent work [56] has demonstrated that citation-based metrics can be used to build a university ranking that correlates highly with peer assessment; we show that our method provides a similar quality of correlation.…”
Section: Introductionmentioning
confidence: 68%
“…We show that our venue scores correlate highly with other influence metrics, such as h-index [24], citations or highly-influential citations [54]. Additionally, we show that university rankings, derived from publication records correlate highly with both established rankings [17,37,42] and with recently published quantitative metrics [6,8,12,56]. arXiv:1904.12573v2 [cs.DL] 5 Jun 2019 2 RELATED WORK Quantitative measures of academic productivity tend to focus on methods derived from citation counts.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations